Bacteria Community Inhabiting Heterobasidion Fruiting Body and Associated Wood of Different Decay Classes - Ren, Wenzi; Penttilä, Reijo; Kasanen, Risto; Asiegbu, Fred O. (Frontiers in Microbiology, 2022)
The microbiome of Heterobasidion-induced wood decay of living trees has been previously studied; however, less is known about the bacteria biota of its perennial fruiting body and the adhering wood tissue. In this study, we investigated the bacteria biota of the Heterobasidion fruiting body and its adhering deadwood. Out of 7,462 operational taxonomic units (OTUs), about 5,918 OTUs were obtained from the fruiting body and 5,469 OTUs were obtained from the associated dead wood. Interestingly, an average of 52.6% of bacteria biota in the fruiting body was shared with the associated dead wood. The overall and unique OTUs had trends of decreasing from decay classes 1 to 3 but increasing in decay class 4. The fruiting body had the highest overall and unique OTUs number in the fourth decay class, whereas wood had the highest OTU in decay class 1. Sphingomonas spp. was significantly higher in the fruiting body, and phylum Firmicutes was more dominant in wood tissue. The FAPROTAX functional structure analysis revealed nutrition, energy, degradation, and plant-pathogen-related functions of the communities. Our results also showed that bacteria communities in both substrates experienced a process of a new community reconstruction through the various decay stages. The process was not synchronic in the two substrates, but the community structures and functions were well-differentiated in the final decay class. The bacteria community was highly dynamic; the microbiota activeness, community stability, and functions changed with the decay process. The third decay class was an important turning point for community restructuring. Host properties, environmental factors, and microbial interactions jointly influenced the final community structure. Bacteria community in the fruiting body attached to the living standing tree was suppressed compared with those associated with dead wood. Bacteria appear to spread from wood tissue of the standing living tree to the fruiting body, but after the tree is killed, bacteria moved from fruiting body to wood. It is most likely that some of the resident endophytic bacteria within the fruiting body are either parasitic, depending on it for their nutrition, or are mutualistic symbionts.